3y+3x-3=0

Simple and best practice solution for 3y+3x-3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y+3x-3=0 equation:


Simplifying
3y + 3x + -3 = 0

Reorder the terms:
-3 + 3x + 3y = 0

Solving
-3 + 3x + 3y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3x + 3 + 3y = 0 + 3

Reorder the terms:
-3 + 3 + 3x + 3y = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 3x + 3y = 0 + 3
3x + 3y = 0 + 3

Combine like terms: 0 + 3 = 3
3x + 3y = 3

Add '-3y' to each side of the equation.
3x + 3y + -3y = 3 + -3y

Combine like terms: 3y + -3y = 0
3x + 0 = 3 + -3y
3x = 3 + -3y

Divide each side by '3'.
x = 1 + -1y

Simplifying
x = 1 + -1y

See similar equations:

| 5x-47=3-7(x+2) | | 6x-8x+8=x-9+17 | | 2.5x+15=4x | | -5/3+1/3=4/3x+4/3x | | -9n+8=-7n-14 | | (y+8)(y-3)= | | .38=log(x) | | -9=-2G | | 4x+5=x+3 | | -8x^2-9x+5=0 | | 4x-30x+16=8 | | 5(5n+4)=195 | | 3+L=5 | | 3.5y-7= | | -3x*45=2x-40 | | -(x+6)=-1-x | | 6m--11=29 | | 5x+(-8y)=12 | | 6y-5=86 | | -36x^2-kx+1=0 | | X+19=-18 | | a^2-24a=16 | | 3+3k=7(k-3) | | x+1/7=2/4 | | 5c+2=2c+7 | | 3x-(x-7)=16 | | 1.5y-6= | | 3.5y+7= | | X-8=-41 | | -3(b-4)=-2 | | 6(-6x+8)=-6(9x-5) | | 39x^2-4x-3= |

Equations solver categories